Implementasi Model Pembelajaran Problem Based Learning untuk Mengembangkan Kemampuan Berpikir Kritis Siswa pada Pembelajaran Akidah Akhlak - Condro Sujalmo; Lamya Hayatina; Amiroh Amiroh (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
This study aims to determine whether the application of the Problem Based Learning model can develop the critikal thinking skills of class XII students in learning Akidah Akhlak at MA Nurul Falah Ciater. The type of research is qualitative with a qualitative descriptive and the subject of this research is students ini class XII MA Nurul Falah Ciater.. Data collection techniques using observation, interviews, and documentation. Data analysis techniques using data reduction, data presentation, data verification, and conclusions. Based on the results of research and data analysis, that the Problem Based Learning model applied to moral akidah learning, can develop the critical thinking skills of XII grade students in learning moral akidah at MA Nurul Falah Ciater. Students are actively engaged in critical thinking problem solving and develop analytical skills. These findings make an important contribution to the developments of effective learning methods in improving students critical thinking skills in the context of learning akidah akhlak. This shows that there is a development of critical thinking skills of XII grade students in learning akidah akhlak by using the problem based learning model.